Seasonal claracteristics of phytoplankton population of the Middle Caspian - S. A. Guseynova (Юг России: экология, развитие, 2015)
In work the seasonal characteristics of phytoplankton are characterized, its quantitative indices, brief history of its studying taxonomic content and biomass distribution